Investigation of Safety Performance of the Workers and the Effective Demographic Charactristics in a Gas Refinery - Fazel Rajabi; Hamidreza Mokarami; Mehdi Jahangiri (Muhandisī-i bihdāsht-i ḥirfah/ī, 2019)
Introduction: Despite the advances in occupational safety, many accidents occur in the workplace. The most of these accidents caused by poor workers safety performance. Knowing the factors that affect safety performance is a suitable guide to planning for occupational accident prevention. This study was conducted to assess workers safety performance and determine its associated demographic factors in a gas refinery. Methods: This cross-sectional and analytical study was carried out on 487 employees of a gas refinery in 2018. In order to assess the safety performance, the Neal and Griffin questionnaires were used. Demographic characteristics were measured by researcher-made questionnaire. to ensure the validity and reliability of the safety performance questionnaire, firstly, psychometric properties of this questionnaire were measured. Then, the relationship between demographic characteristics and safety performance was assessed by one-way ANOVA and independent sample t-test using SPSS version 23 software. Results: The primary results of this study showed that the safety performance questionnaire has a desirable validity and reliability. Also, workers safety performance was at the desired level. Among the demographic characteristics, the relation between age and job experience with safety performance were significant (p-value<0.05). Young people had a weaker safety performance than elderly people. Conclusion: Considering the weaker safety performance of young and low experienced workers and older and high experience workers, it is necessary to pay more attention to these two groups in workplace safety planning.